Advancements in Epidemiological Methods: A Comprehensive Review of Contemporary Approaches - Taheri, Shiva; Taheri , Behzad (Health Nexus, 2023)
This review article systematically examines the significant advancements in epidemiological methods from 2005 to 2023, highlighting the evolution and impact of contemporary approaches in the field. Employing a thorough literature search across key databases, the review focuses on peer-reviewed articles, reviews, and meta-analyses that underscore innovative methodologies and applications in epidemiology. The inclusion criteria prioritized studies that introduced new techniques, integrated technology, or applied interdisciplinary approaches. This article synthesizes these advancements, revealing trends such as the incorporation of big data analytics, machine learning, and genetic epidemiology, which have substantially enhanced the scope and accuracy of epidemiological research. The review also discusses the challenges and ethical considerations emerging from these advanced methods, particularly in data privacy and the complexity of analysis. The findings underscore the shift towards more dynamic, precise, and interdisciplinary methods in epidemiology, reflecting the field’s adaptation to the demands of modern public health challenges. This comprehensive overview not only provides a valuable resource for epidemiologists and public health professionals but also sets the stage for future research directions, emphasizing the need for continued innovation and ethical vigilance in epidemiological practices.